Virial coefficients and vapor-liquid equilibria of the EXP6 and 2-Yukawa fluids - Krejčí, J.; Nezbeda, I.; Melnyk, R.; Trokhymchuk, A. (Condensed Matter Physics, 2011)
Virial coefficients B₂ through B₄ and the vapor-liquid equilibria for the EXP6 and 2-Yukawa (2Y) fluids have been determined using numerical integrations and Gibbs ensemble simulations, respectively. The chosen 2Y models have been recently determined as an appropriate reference fluid for the considered EXP6 models.